Contact Investigation of Children Exposed to Tuberculosis in South East Asia: A Systematic Review. (15th November 2011) - Triasih, Rina; Rutherford, Merrin; Lestari, Trisasi; Utarini, Adi; Robertson, Colin F.; Graham, Stephen M.
Abstract : Background . Screening of children who are household contacts of tuberculosis (TB) cases is universally recommended but rarely implemented in TB endemic setting. This paper aims to summarise published data of the prevalence of TB infection and disease among child contacts in South East Asia. Methods . Search strategies were developed to identify all published studies from South East Asia of household contact investigation that included children (0–15 years). Results . Eleven studies were eligible for review. There was heterogeneity across the studies. TB infection was common among child contacts under 15 years of age (24.4–69.2%) and was higher than the prevalence of TB disease, which varied from 3.3% to 5.5%. Conclusion . TB infection is common among children that are household contacts of TB cases in South East Asia. Novel approaches to child contact screening and management that improve implementation in South East Asia need to be further evaluated.